Gestión operativa y su incidencia en el servicio de atención a los usuarios del terminal terrestre ¨gilberto gordillo ruíz¨, cantón ventanas, año 2023. - VITERI MORA, KELLY KARINA (2025)
The present research work was carried out with the purpose of analyzing the operational management of the ¨Gilberto Gordillo Ruíz¨ land terminal and its impact on the attention to its users. For which a descriptive and exploratory research was carried out, together with a mixed approach (qualitative and quantitative). Regarding the population, it was composed of 1,474,661 people who used the services of the facility during the year 2023, and additionally, 32 collaborators. When applying the sample size calculation, a total of 384 users were surveyed. On the other hand, the techniques applied were the interview, survey and observation, while the instruments used included the observation guide, the questionnaire (using the Servqual model) and the observation form. According to the results obtained, the facility complies with 60% of the criteria that were evaluated, while the remaining 40% reflect critical areas that require and need immediate improvement. On the other hand, 97% of the employees considered that the terminal facilities are well maintained for the users. In addition, 64% of the users surveyed agreed with the state of maintenance and cleanliness of the facilities at the terminal.